ANALISIS PERBEDAAN KADAR BESI (Fe) MENGGUNAKAN SERBUK CANGKANG TELUR PADA AIR SUMUR GALI - Fitria Fatma (HUMAN CARE JOURNAL, 2022)
Water is the most important substance for the human body after air. Water is used for many things such as washing, cooking, drinking and others. The aim of this research was to analyze Iron (Fe) Levels Differences by Using Egg Shells as Adsorbent. The type of this research was Experimental method by using Posttest Only Design approach. The results of the research found that giving egg shell powder of 5 grams, 7 grams and 9 grams to sample A, B and C (p-value 0,952 , 0,729 and 0,118)were able to reduce iron (Fe) levels in water. However, it did not meet the clean water requirements that have been set because the results obtained are iron (Fe) levels are still above 1 mg/l. It can be cocluded that giving 5 grams, 7 grams, and 9 grams of eggshell powder in well water can reduce iron (Fe) levels. It is recommended for the community to be able to utilize eggshell powder in reducing iron (Fe) levels in well water.